2022
DOI: 10.1007/s12662-022-00851-w
|View full text |Cite
|
Sign up to set email alerts
|

Positive influence of neuromuscular training on knee injury risk factors during cutting and landing tasks in elite youth female handball players

Abstract: Anterior cruciate ligament (ACL) ruptures are frequent in the age group of 15–19 years, particularly for female athletes. Although injury-prevention programs effectively reduce severe knee injuries, little is known about the underlying mechanisms and changes of biomechanical risk factors. Thus, this study analyzes the effects of a neuromuscular injury-prevention program on biomechanical parameters associated with ACL injuries in elite youth female handball players. In a nonrandomized, controlled intervention s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Additionally, Hosseini et al found that combining a fatigue protocol with an unanticipated condition resulted in a smaller knee flexion angle and increased knee valgus angle in the non-dominant leg compared to the dominant leg during COD [ 21 ]. Similarly, Schmidt et al demonstrated that in unanticipated conditions, fatigue caused the knee of the non-dominant leg in female handball players to be more extended during jumping and cutting movements [ 42 ]. Previous research suggests that the combination of fatigue and decision-making hampers proprioceptive receptor function, increasing the risk of injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Hosseini et al found that combining a fatigue protocol with an unanticipated condition resulted in a smaller knee flexion angle and increased knee valgus angle in the non-dominant leg compared to the dominant leg during COD [ 21 ]. Similarly, Schmidt et al demonstrated that in unanticipated conditions, fatigue caused the knee of the non-dominant leg in female handball players to be more extended during jumping and cutting movements [ 42 ]. Previous research suggests that the combination of fatigue and decision-making hampers proprioceptive receptor function, increasing the risk of injury.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers stated that the FAST-FP or multidirectional functional protocol recruited various muscle groups, while the SLO-FP primarily affected flexors and extensors [ 51 ]. Schmidt et al also discovered that functional fatigue affected the initial knee flexion angle of the non-dominant limb in all tasks [ 42 ]. Moreover, significant changes were observed in the initial knee flexion angle of the dominant limb, the initial and maximum hip flexion angle, and the maximum knee flexion angle of the non-dominant leg during the cutting task [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation